Perawatan Bahan Pustaka pada Perpustakaan Umum Kabupaten Deli Serdang - Auliyanti, Tuti Aulia; Sumanti, Solihah Titin; Yusniah, Yusniah (Al-DYAS, 2025)
This research aims to determine how employees of the Deli Serdang Regency Public Library maintain the library materials there and the challenges or obstacles they face in doing so. This type of research uses qualitative and descriptive methodology. Data collection methods use observation, interviews, and documentation. Purposive sampling, which is used in this research, is to identify informants. Technical data analysis is carried out in four ways, namely data reduction, data presentation, and drawing conclusions. From the results of the research conducted by the researcher, it can be concluded that the maintenance of library materials carried out by the Deli Serdang Regency Public Library is repairing damaged books by covering books, sewing, maintaining cleanliness on the bookshelves, and making appeals to users to work together to maintain and keep the books. The obstacles faced in maintaining library materials at the Deli Serdang Regency Public Library are equipment that are still minimal and inadequate, lack of human resources, and lack of awareness of the users themselves.